Identification of environmental impact and its consequences in the city of Huanuco - Contreras-Zarco, Ella V. (2023)
In the present study, the environmental impacts of the city of Huánuco were identified, as well as their consequences, through the use of a qualitative approach and non-experimental design, using the techniques of observation, description and explanation. The objective of the study was to identify and describe the environmental impact produced by natural factors and human actions in the city. Likewise, specify the consequences that affect the well-being of the inhabitants, in addition to the dangers that threaten their safety. The results reflect that there is a negative environmental impact on the ecosystem, air, water, soil, landscapes and the health of the population, which can become possible contingencies that threaten the city. In conclusion, there is a serious problem that is evident in the deterioration and degradation of biodiversity, especially due to the occupation of vulnerable areas with the construction of houses around the city.